2006
DOI: 10.3354/meps308197
|View full text |Cite
|
Sign up to set email alerts
|

Field evidence for an association between growth and protein polymorphism in the acorn barnacle Semibalanus balanoides

Abstract: Organisms living in highly heterogeneous environments are useful for examining the effects of associations between phenotypes and ecologically relevant genes in the field. Here, we tested the null hypothesis of no association between the variation in 2 fitness-related traits (growth and fecundity) and polymorphism at 2 enzymatic loci, MPI* and GPI*, known to be subject to strong spatial selection. We also tested if such an association was related to the intensity of genotype selection observed for both allozym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…These results support those of Véliz et al (2006a), who suggested a 2-stage selection process consisting of genotype-specific mortality shortly after settlement, followed by a genotype-specific growth association in later life. Opercular width is a classic measurement of barnacle size; however, cirral length is expected to be an important fitness trait due to its relationship with resource acquisition in filter feeding.…”
Section: Genetic Effectssupporting
confidence: 81%
See 2 more Smart Citations
“…These results support those of Véliz et al (2006a), who suggested a 2-stage selection process consisting of genotype-specific mortality shortly after settlement, followed by a genotype-specific growth association in later life. Opercular width is a classic measurement of barnacle size; however, cirral length is expected to be an important fitness trait due to its relationship with resource acquisition in filter feeding.…”
Section: Genetic Effectssupporting
confidence: 81%
“…Opercular width is a classic measurement of barnacle size; however, cirral length is expected to be an important fitness trait due to its relationship with resource acquisition in filter feeding. Previous links between size and genotype have been documented at both the Mpi and Gpi loci (Schmidt 2001, Véliz et al 2006a. In the present study, Mpi-SS homozygotes represented the largest class of individuals among fieldcollected barnacles in the first 2 mo after settlement.…”
Section: Genetic Effectsmentioning
confidence: 56%
See 1 more Smart Citation
“…First, mating among acorn barnacles can only take place when one individual is within penile distance from other potential mates (Anderson 1994). Moreover, the acorn barnacle is a highly fecund hermaphrodite, each adult producing up to 5000 larvae (Véliz et al . 2006a).…”
Section: Discussionmentioning
confidence: 99%
“…The differential fitness of MPI genotypes was only realized when barnacles were exposed to both dietary mannose and temperature/desiccation stress, and patterns of survivorship were associated with functional differences between MPI genotypes (Schmidt 2001; Rand et al . 2002; but see Veliz et al . 2006).…”
Section: Discussionmentioning
confidence: 99%